Three-dimensional BiVO4-based semiconductor photocathode for high efficiency photo-assisted Zn-iodine redox flow batteries. (25th June 2022) - Dong, Maolin; Wang, Yijie; Li, Aoshuang; Cheng, Chuanwei
Abstract: Aqueous Zn-iodine redox flow batteries have aroused great interest for the features of high capacity, excellent stability, low cost, and high safety, yet the dissatisfying energy efficiency still limits their future advancement. In this work, three-dimensional semiconductor BiVO4 nanoparticles decorated hierarchical TiO2 /SnO2 arrays (BiVO4 @TiO2 /SnO2 ) were applied as photocathode in Zn-iodine redox flow batteries (ZIRFBs) for the realization of efficient photo-assisted charge/discharge process. The photogenerated carriers at the solid/liquid interfaces boosted the oxidation process of I −, and thus contributed to a significant elevation in energy efficiency of 14.9% (@0.5 mA cm −2 ). A volumetric discharge capacity was extended by 79.6% under light illumination, owing to a reduced polarization. The photocathode also exhibited an excellent durability, leading to a stable operation for over 80 h with a maintained high energy efficiency of ∼90% @0.2 mA cm −2 . The research offers a feasible approach for the realization of high-energy-efficiency aqueous Zn-iodine batteries towards high-efficiency energy conversion and utilization.